Expression of gonadotropin-releasing hormone receptors and autocrine regulation of neuropeptide release in immortalized hypothalamic neurons. - Krsmanović, L Z (1993)
The hypothalamic control of gonadotropin secretion is mediated by episodic basal secretion and midcycle ovulatory surges of gonadotropin-releasing hormone (GnRH), which interacts with specific plasma membrane receptors in pituitary gonadotrophs. Similar GnRH receptors and their mRNA transcripts were found to be expressed in immortalized hypothalamic neurons, which release GnRH in a pulsatile manner in vitro. Activation of these neuronal GnRH receptors elicited dose-related intracellular Ca2+ concentration responses that were dependent on calcium mobilization and entry and were inhibited by GnRH antagonists. Exposure of perifused neurons to a GnRH agonist analog caused a transient elevation of GnRH release and subsequent suppression of the basal pulsatile secretion. This was followed by dose-dependent induction of less frequent but larger GnRH pulses and ultimately by single massive episodes of GnRH release. The ability of GnRH to exert autocrine actions on its secretory neurons, and to promote episodic release and synchronized discharge of the neuropeptide, could reflect the operation of the endogenous pulse generator and the genesis of the preovulatory GnRH surge in vivo.